Studying the Nature of Recent Marine Sediments on the Accumulation of Cadmium and Lead in Latakia and Baniyas Shore - الخريط, بدور; سامر غدير; حسام الدين لايقه (Latakia University Journal -Basic Sciences Series, 2024)
This research based on the determination of some trace heavy metals (Lead (Pb), cadmium (Cd)), in different types of recent marine sediments and studying their grained isolation along different zones of Latakia and Baniyas shore area during summer period of 2022 using (Atomic Absorption Spectrometry: AAS). Moreover this research aimed to determine the correlation between The following factors, quality and nature of the sediment also the effect of the grained particle diameter on the change of these concentrations. The results indicate that there is a significant correlation between the change in the concentrations of the studied metal elements (lead (Pb) and cadmium (Cd)) and the nature and quality of the sediment, where it was observed almost complete dominance of sands, moderate isolation, and with a very negative slope in the shore of Latakia city, which indicates relatively moderate energy conditions compared to the predominance of gravel sands, with poor sorting, excessive and with a very negative slope, which indicates high energy conditions in Baniyas beach.